Adoption of mobile banking services in Turkey - Çakıcı, Simge (My University, 2008)
TÜRKİYE’DE MOBİL BANKACILIK HİZMETLERİNİN ADAPTASYONU Hemen hemen tüm bankalar fiziki şubeler dışında ATM, telefon bankacılığı, internet şubesi, TV şubesi ve kiosk gibi pek çok kanaldan hizmet vermektedir. Günümüzde “mobil” de bankacılık için olmazsa olmaz bir kanal haline gelmektedir. Bu sebeple mobil bankacılık kullanım eğilimini etkileyen faktörlerin bulunması için araştırma yapılması ihtiyacı doğmuştur. Teknoloji adaptasyon modellerindeki kısıtlar ve bazı kavramların araştırma modeline eklenmesi gerektiği düşünüldüğünden, bu modeller ek kavramlar ile modifiye edilmiştir. Bu tezin amacı, literatür taramasından yola çıkarak ve teknoloji adaptasyon modellerini baz alarak, Türk müşterilerin mobil bankacılık servislerinin adaptasyonunda hangi faktörlerden etkilediğini araştırmaktadır. Anketler Türkiye’de yapılmıştır. Cevaplayanlar Antalya, Ankara ve çoğunlukla İstanbul’da yaşayan kişilerden oluşmaktadır. Anketleri cevaplayandan 201 kişi de 22 yaşından büyük ve banka kullanıcısıdır. Araştırma sonuçları bankacılık işlemlerini mobil olarak gerçekleştirmek için yüksek oranda bir istek olduğunu göstermektedir. Çalışma sonucunda eğilim, iç etkiler ve algılanan kullanışlılığın kullanım niyetine güçlü etkileri olduğu bulunmuştur. Ayrıca eğilim, öznel normlar ve kişiselleştirme de kullanım niyetini etkilemektedir.

ADOPTION OF MOBILE BANKING SERVICES IN TURKEY Almost all the banks are giving service from lots of channels in addition to brick and mortar branchs, like ATMs, call centers, online via internet, tv channel, kiosks. Today the mobile is also becoming a “must” channel for banks. Therefore research for finding the factors that influence consumers intention to use mobile banking is needed. Because of the limitations of main technology acceptance models, they are modified with additional dimensions. This thesis explores the factors that influence Turkish customers to adopt the mobile banking services, by the literature review and technology acceptance models. Survey was conducted in Turkey, the respondents were living in Antalya, Ankara and mostly in İstanbul. Sample of the study is 201 respondents, all of them are bank users and older than 22 years old. The findings suggest that desire for making transactions from mobile channel is very high. The study shows the strong impact of attitude, perceived usefulness, identification, trust, internal influences and perceived ease of use on use intention of mobile banking in Turkey. Differences according to demographics are also important. By the results it is seen that men have better access to facilitating conditions and behavioral control for using mobile banking than women. Attitude, identification, perceived ease of use, perceived usefullness, internal influences, trust, self efficiency and subjective norm have positive effect on use intention and actual use and are suggested to be used in further research.
Keywords: Adaptasyon; Bankalar ve Bankacılık; Bankalar ve Bankacılık_Türkiye; Mobil Bankacılık; Üretim Yönetimi